Metabolic Blockade-Based Genome Mining of Malbranchea circinata SDU050: Discovery of Diverse Secondary Metabolites - Hu Yang; Xiaowei Luo; Zhuo Shang; Kunlong Li; Jian Cai; Yingying Chen; Longchao Xin; Jianhua Ju (Marine Drugs)
Malbranchea circinata SDU050, a fungus derived from deep-sea sediment, is a prolific producer of diverse secondary metabolites. Genome sequencing revealed the presence of at least 69 biosynthetic gene clusters (BGCs), including 30 encoding type I polyketide synthases (PKSs). This study reports the isolation and identification of four classes of secondary metabolites from wild-type M. circinata SDU050, alongside five additional metabolite classes, including three novel cytochalasins (7–9), obtained from a mutant strain through the metabolic blockade strategy. Furthermore, bioinformatic analysis of the BGC associated with the isocoumarin sclerin (1) enabled the deduction of its biosynthetic pathway based on gene function predictions. Bioactivity assays demonstrated that sclerin (1) and (−)-mycousnine (10) exhibited weak antibacterial activity against Gram-positive bacteria such as Staphylococcus aureus, methicillin-resistant Staphylococcus aureus (MRSA), and Bacillus subtilis. These findings underscore the chemical diversity and biosynthetic potential of M. circinata SDU050 and highlight an effective strategy for exploring marine fungal metabolites.